Turning crisis into opportunity in the Gig economy: acceptance of e-Hailing food delivery applications in Malaysia / Purnomo M Antara ... [et al.] - M Antara, Purnomo; Mohamad, Abdullah; Othman, Kamarudin; Wahab, Muhammad Zarunnaim; Ibrahim, Nadhrathul Ain; Musa, Rosidah; Ningrum, Nonik Kusuma (2022)
The negative impact of the COVID-19 pandemic has given people the opportunity to move forward. The increasing number of app-based online ordering systems creates significant job opportunities for freelancers and the jobless impacted by the COVID-19 pandemic. The scenario has brought about a Gig-economy in the Malaysian context. This study aims to examine and explain consumers' behavioural usage of e-hailing food delivery applications in Malaysia using the Technology Acceptance Model (TAM). One hundred respondents completed the structured survey questionnaires. The study found that perceived usefulness and perceived ease of use positively affect the behavioural intention to use e-hailing food delivery applications. Besides, behavioural intention also positively affects actual usage. The study suggests that the government or policymakers could give more attention to this fast-growing industry.